PELAKSANAAN DINDING PENAHAN TANAH CANTILEVER DAN GRAVITY PADA FLY OVER - Winata, Wiyeo; Rosyad, Farlin (Ensiklopedia of Journal, 2024)
1) With the rapid development in South Sumatra Province, the government is implementing development policies in the civil construction sector. This is very necessary to increase development progress in various fields and to provide complete and adequate facilities according to the needs of its users. We often find that roads will be cut off somewhere due to natural obstacles or because of construction needs due to increasing population development. With the purposes outlined above, bridge construction is being carried out in several regions of South Sumatra. The government carried out the PUPR Bina Marga service to build a bridge at PPK 3.3 (Fly Over Bantaian, Gunung Megang District, Muara Enim District). 2) The construction of retaining walls has a very important role on slopes, including: resisting the lateral pressure of active soil which has the potential for landslides, resisting the lateral pressure of water which has the potential for the soil to collapse due to large water pressure, and preventing water seepage due to high elevations. on a slope. A slope on which a structure will be placed needs to be strengthened using a retaining wall. The data used as reference material in preparing this Independent Study Proposal can be classified into two types, namely: Primary Data, Secondary Data 3) Quality implementation in a development project needs to be carried out, because the quality used will affect the time and costs required. Quality control is carried out so that the work carried out by the contractor is in accordance with what has been planned by the planning consultant. Quality control can be carried out directly or indirectly. Direct control can be carried out directly in the field and indirect control can be carried out through laboratory checks. 4) Based on the results of an independent study in the field on the construction of the Bantaian Muara Enim FO, which was discussed in the previous chapter, the following conclusions can be drawn: 1) The length of the Bantaian Muara Enim FO is from STA 147+050 – STA 147+700. 2) Retaining wallCantilever has STA 147+575 – STA 147+615 andGravity STA 147+418. 3) Several stages of retaining wall implementation work.